2012
DOI: 10.1007/s00468-012-0698-3
|View full text |Cite
|
Sign up to set email alerts
|

Stem CO2 efflux of ten species in temperate forests in Northeastern China

Abstract: Stem CO 2 efflux (E S ) is an important component of forest ecosystem carbon budgets and net ecosystem CO 2 exchange, but little is known about E S in temperate forests in Northeastern China, an area with a large extent of forest. We measured E S along with stem temperature at 1 cm depth (Ts) over a 9 month period in 2007 on ten dominant tree species of secondary forests of the region. Other measurements included the autotrophic component of soil CO 2 efflux (E A ) and stem diameter at breast height (DBH). Our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
3
10
0
2
Order By: Relevance
“…In conclusion, the stem CO 2 efflux increased with the temperature of the woody tissue, as many other studies have found (Teskey et al, 2008;Brito et al, 2010Brito et al, , 2013Yang et al, 2012). Thus, the stem CO 2 efflux increased according to the following series: winter, autumn, spring and summer.…”
Section: Discussionsupporting
confidence: 60%
“…In conclusion, the stem CO 2 efflux increased with the temperature of the woody tissue, as many other studies have found (Teskey et al, 2008;Brito et al, 2010Brito et al, , 2013Yang et al, 2012). Thus, the stem CO 2 efflux increased according to the following series: winter, autumn, spring and summer.…”
Section: Discussionsupporting
confidence: 60%
“…The Q 10 values of stem CO 2 efflux in the present study were similar to those reported for other species (Zha et al 2004;Yang et al 2012b;Rodríguez-Calcerrada et al 2014). However, we found that pruning does not alter the Q 10 values of stem CO 2 efflux, which was contrary to our third hypothesis.…”
Section: Temperature Responsesupporting
confidence: 90%
“…As our partial correlation analysis based on GPP and MAT could not fully explain the relationship of annual E S and R A , we suggest that CO 2 transport in the xylem should be considered as an additional source of CO 2 contributing to E S . Although such a mechanism has been mostly described in studies with short‐term measurement periods and in forests of a relatively young stand age, it was also implicated in one study of mature temperate forest stands (from 39 to 56 years old) (Yang et al ., ) and could be an additional factor contributing to the variation in E S and R A observed in our study.…”
Section: Discussionmentioning
confidence: 59%